Chemoprevention in oral leukoplakia: challenges and current landscape - Palma, Victor de Mello; Koerich Laureano, Natalia; Frank, Luiza Abrahão; Rados, Pantelis Varvaki; Visioli, Fernanda (Frontiers in Oral Health, 2023)
Oral potentially malignant disorders have the potential to transform into oral cancer. Oral leukoplakia is a prevalent disorder with a 9.8% malignant transformation rate. The standard management for OL involves surgical excision, but its efficacy in preventing clinical recurrence and malignant transformation is limited. Therefore, alternative strategies such as chemoprevention modalities have emerged as a promising approach to inhibit the carcinogenesis process. The aim of this review was to identify human studies that investigated the effectiveness of chemopreventive agents in preventing the progression of oral leukoplakia and to provide guidance for future research. Several systemic and topical agents have been evaluated for their potential chemopreventive effects in oral leukoplakia. Systemic agents that have been investigated include vitamin A, lycopene, celecoxib, green tea extract, ZengShengPing, Bowman Birk inhibitor, beta-carotene, curcumin, erlotinib, and metformin. In addition, topical agents tested include bleomycin, isotretinoin, ONYX-015 mouthwash, ketorolac, and dried black raspberry. Despite numerous agents that have already been tested, evidence supporting their effectiveness is limited. To improve the search for an ideal chemopreventive agent for oral leukoplakia, we propose several strategies that can be implemented. Oral leukoplakia chemoprevention presents a promising opportunity for decreasing the incidence of oral cancer. Identifying new chemopreventive agents and biomarkers for predicting treatment response should be a focus of future research.